2011
DOI: 10.13057/biodiv/d130109
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Forest Biodiversity and Rattan Jernang (Daemonorops draco) sustainable harvesting by Anak Dalam tribe in Jambi, Sumatra

Abstract: Adiwibowo A, Sulasmi IS, Nisyawati. 2012 Jambi,. Conservation of tropical trees can be achieved if supported by the sustainable use of forest by community live nearby through harvesting of non timber woods, for instance rattan. Furthermore, rattan jernang individuals and trees have significant associations. Therefore, objective of this paper is to investigate the utilization of rattan jernang (Daemonorops draco Wild) related to the forest tree biodiversity by Anak Dalam tribe in several villages in Jambi, Suma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Cultivation trials on many of the Southeast Asia species, as well as recent germination trials of the African taxa, have indicated that seeds will germinate under a wide range of light conditions. The resultant seedlings will remain for long periods on the forest floor awaiting sufficient light for them to develop, such as a tree fall (Adiwibowo, Sulasmi & Nisyawati, 2012). Rattans can be clustering (clumpforming) or solitary.…”
Section: Figure 10 Fruit and Seed Structure Of Calamus Merriliimentioning
confidence: 99%
“…Cultivation trials on many of the Southeast Asia species, as well as recent germination trials of the African taxa, have indicated that seeds will germinate under a wide range of light conditions. The resultant seedlings will remain for long periods on the forest floor awaiting sufficient light for them to develop, such as a tree fall (Adiwibowo, Sulasmi & Nisyawati, 2012). Rattans can be clustering (clumpforming) or solitary.…”
Section: Figure 10 Fruit and Seed Structure Of Calamus Merriliimentioning
confidence: 99%